2005
DOI: 10.1111/j.1742-4658.2005.04555.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of a Coenzyme A disulfide reductase from Pyrococcus horikoshii

Abstract: While surveying the genomes of hyperthermophilic and thermophilic Archaea for homologues of the flavoprotein disulfide reductases, many homologues with a high degree of identity to the branch of this family represented by glutathione reductase were found [1]. Most of the homologues appear to belong to the subfamily that depend on a redox-active single cysteine, analogous to the NADH oxidase and per-oxidase of Enterococcus and the coenzyme A disulfide reductase (CoADR; EC 1.8.1.14) of Staphylococcus Corresponde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 27 publications
9
66
1
Order By: Relevance
“…GSH, on the other hand, is not produced by the Archaea; it is also absent in many Bacteria. Harris et al (58) recently reported that CoASH is the major low-molecular weight thiol in the hyperthermophilic archaeon Pyrococcus furiosus, and the recombinant form of a CoADR from Pyrococcus horikoshii has been characterized. The enzyme exhibits a preference for NADPH in the reduction of CoAD, but questions remain regarding both the identity of the nonflavin redox center and the high NAD(P)H oxidase activity observed in the presence of FAD.…”
Section: Coadr Homologs In Bacteria and Archaeamentioning
confidence: 99%
“…GSH, on the other hand, is not produced by the Archaea; it is also absent in many Bacteria. Harris et al (58) recently reported that CoASH is the major low-molecular weight thiol in the hyperthermophilic archaeon Pyrococcus furiosus, and the recombinant form of a CoADR from Pyrococcus horikoshii has been characterized. The enzyme exhibits a preference for NADPH in the reduction of CoAD, but questions remain regarding both the identity of the nonflavin redox center and the high NAD(P)H oxidase activity observed in the presence of FAD.…”
Section: Coadr Homologs In Bacteria and Archaeamentioning
confidence: 99%
“…The tk1481 gene consisted of 1,344 bp and encoded a protein of 448 amino acids with a predicted molecular mass of 48,780 Da. The deduced amino acid sequence shared 24 to 33% identity with the other six NOX paralogs in T. kodakarensis and showed 31 to 35% identity with previously reported NOXs from hyperthermophiles, including H 2 O 2 -H 2 O-forming NOX1 from P. furiosus (PF1532) (33%) (38), H 2 O 2 -forming NoxA-2 from A. fulgidus (AF0395) (32%) (28), H 2 O-forming NOX from Thermococcus profundus (31%) (14), CoADR from P. horikoshii (PH0572) (31%) (11), and NAD(P)H:elemental sulfur oxidoreductase from P. furiosus (PF1186) (35%) (34). The homology of TK1481 with well-studied NOXs from mesophiles was lower, as demonstrated by the 27 to 28% identity with H 2 O-forming NOXs from L. sanfranciscensis (18), Streptococcus mutans (12), and Enterococcus faecalis (29) and the 25% identity with H 2 O 2 -forming NOX from S. mutans (12).…”
Section: Resultsmentioning
confidence: 91%
“…In an NADP-utilizing enzyme the C-terminal Gly of this motif is replaced with Ala, Pro or Ser, perhaps to accommodate the pyrophosphate group of NADP (Bellamacina, 1996). It should be noted that CoADRs from Bacillus anthracis and P. horikoshii carry the GXGXXG motif, yet oxidize both NADH and NADPH (Harris et al, 2005;Wallen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these non-methanogenic archaea might use Nox homologues to counter the toxic effect of the molecular oxygen that they could be exposed to in their natural habitats (Kengen et al, 2003;Ward et al, 2001). Also, in Pyrococcus horikoshii and Pyrococcus furiosus, a Nox homologue has been demonstrated to act as a coenzyme A disulfide reductase (CoADR) (Harris et al, 2005) as well as sulfur reductase (Schut et al, 2007). None of the methanogen Nox homologues have been investigated for their catalytic or in vivo functions.…”
Section: Introductionmentioning
confidence: 99%